Food Inflation in Sub-Saharan Africa : Causes and Policy Implications - Alper, Emre (IMF Working Papers; Working Paper ;, 2016)
This paper analyzes food inflation trends in Sub-Saharan Africa (SSA) from 2000 to 2016 using two novel datasets of disaggregated CPI baskets. Average food inflation is higher, more volatile, and similarly persistent as non-food non-fuel (NF/NF) inflation, especially in low-income countries (LICs) in SSA. We find evidence that food inflation became less persistent from 2009 onwards, related to recent improvements in monetary policy frameworks. We also find that high food prices are driven mainly by non-tradable food in SSA and there is incomplete pass-through from world food and fuel prices and exchange rates to domestic food prices. Taken together, these finding suggest that central banks in low-income countries with high and persistent food inflation should continue to pay attention to headline inflation to anchor inflation expectations. Other policy levers include reducing tariffs and improving storage and transport infrastructure to reduce food pressures.